2012
DOI: 10.1021/jp2108939
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Observation of Multiple Phase Transitions in Low-Melting Ionic Liquid [BMIM][BF4] under High Pressure up to 30 GPa

Abstract: In situ characterization of phase transitions and direct microscopic observations of a low-melting ionic liquid, 1-butyl-3-methyl imidazolium tetrafluoroborate ([BMIM][BF(4)]), has been performed in detail by Raman spectroscopy. Compression of [BMIM][BF(4)] was measured under hydrostatic pressure up to ~30.0 GPa at room temperature by using a high-pressure diamond anvil cell. With pressure increasing, the characteristic bands of [BMIM][BF(4)] displayed nonmonotonic pressure-induced frequency shifts, and it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 23 publications
0
29
0
1
Order By: Relevance
“…Previous high‐pressure Raman spectroscopy studies have shown crystal phase transitions of [C 4 C 1 Im]Cl and [C 4 C 1 Im]Br, and liquid–crystal transition of [C 4 C 1 Im]PF 6 below 1.0 GPa . In contrast, no crystallization of [C 4 C 1 Im]BF 4 has been observed even at 30.0 GPa . Interestingly, in case of ionic liquids based on the N,N‐diethyl‐N‐methyl‐N‐(2‐methoxyehtyl)ammonium cation, crystallization was observed at 1.2 GPa for the case of BF 4 ‐ anion, whereas crystallization was not observed for the case of [Tf 2 N] ‐ anion even at 5.5 GPa .…”
Section: Resultsmentioning
confidence: 94%
“…Previous high‐pressure Raman spectroscopy studies have shown crystal phase transitions of [C 4 C 1 Im]Cl and [C 4 C 1 Im]Br, and liquid–crystal transition of [C 4 C 1 Im]PF 6 below 1.0 GPa . In contrast, no crystallization of [C 4 C 1 Im]BF 4 has been observed even at 30.0 GPa . Interestingly, in case of ionic liquids based on the N,N‐diethyl‐N‐methyl‐N‐(2‐methoxyehtyl)ammonium cation, crystallization was observed at 1.2 GPa for the case of BF 4 ‐ anion, whereas crystallization was not observed for the case of [Tf 2 N] ‐ anion even at 5.5 GPa .…”
Section: Resultsmentioning
confidence: 94%
“…19,20 Ionic liquids under high pressure have been studied by Raman spectroscopy in the high frequency range of intramolecular normal modes. These studies showed conformational changes, 21,22 phase transitions, [23][24][25] and enhancement of anion-cation hydrogen bonding interactions, 26 for several ionic liquids under high pressure. However, in the authors' knowledge, there is no previous study concerning the effect of pressure on the low frequency range of Raman or OKE spectra of ionic liquids.…”
Section: Introductionmentioning
confidence: 94%
“…In the case of imidazolium-based ILs, which is one of the most studied ILs, high-pressure phase behavior of some 1-alkyl-3-methylimidazolium tetrafluoroborate ([C n MIM][BF 4 ]) have been investigated in previous studies [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%